2018
DOI: 10.1016/j.engstruct.2018.07.022
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and numerical studies on the structural response of normal strength concrete slabs subjected to blast loading

Abstract: To assess the blast performance of concrete structures, a shock tube has been used to simulate blast loading against concrete slabs of two different mixes ordered as C45/55 and C20/25. The C45/55 slabs were tested without reinforcement, whereas the C20/25 slabs were tested both with and without reinforcement to investigate the effect of adding steel bars on the structural response. The performance of the shock tube itself was also evaluated. Compression tests on cubes and cylinders of both concrete recipes wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(8 citation statements)
references
References 49 publications
0
8
0
Order By: Relevance
“…Mao et al [20] observed that with the increase of fiber volume in Ultra high-performance fiber-reinforced concrete slab, the deflection in the slab is decreasing therefore, it indicates the increased blast resistance of UHPFRC slab. Kristoffersen et al [21] found that the strains and the damage in the concrete slabs were reduced in the analysis when steel-bar reinforcement was included against the blast loading. Based on the results available in the literature, the response of slab in terms of spall radius corresponding to various charge weights is shown in Fig.…”
Section: Literature On the Experimental Studiesmentioning
confidence: 99%
“…Mao et al [20] observed that with the increase of fiber volume in Ultra high-performance fiber-reinforced concrete slab, the deflection in the slab is decreasing therefore, it indicates the increased blast resistance of UHPFRC slab. Kristoffersen et al [21] found that the strains and the damage in the concrete slabs were reduced in the analysis when steel-bar reinforcement was included against the blast loading. Based on the results available in the literature, the response of slab in terms of spall radius corresponding to various charge weights is shown in Fig.…”
Section: Literature On the Experimental Studiesmentioning
confidence: 99%
“…The pipe was meshed by 8-node linear brick elements with reduced integration. An element size of about 10 mm was used (about 55000 elements in total), offering a fair compromise between speed and accuracy [6]. The "concrete damage plasticity model" in ABAQUS [8], based on the work by Lubliner et al [11] and Lee and Fenves [12], was used to represent the concrete material.…”
Section: Numerical Setupmentioning
confidence: 99%
“…The "concrete damage plasticity model" in ABAQUS [8], based on the work by Lubliner et al [11] and Lee and Fenves [12], was used to represent the concrete material. The calibration was based on previsously obtained material data [6,13], and scaled according to the data provided by the manufacturer. The material has separate damage parameters for compressive and tensile damage.…”
Section: Numerical Setupmentioning
confidence: 99%
See 1 more Smart Citation
“…Another direction is the modification technology of concrete structure through the introduction of low hard porous disperse components (damping additives) into the concrete mix. This approach to the increase of concrete impact endurance was studied by R. Oyguc [1], M. Kristoffersen [2], A. Maazoun [3], Z.I. Syed [4], K. Makita [5], etc.…”
Section: Introductionmentioning
confidence: 99%